Pengaruh Penambahan Kombinasi Naa Dan Bap Terhadap Pertumbuhan Protocorm Like Bodies (Plb) Anggrek Dendrobium Sp. Secara In Vitro - Lisnawati Lisnawati (Peneliti.net, 2022)
The research was conducted at the biotechnology laboratory Faculty of Agriculture Winaya Mukti University Sumedang from August to November 2020. Methods of research using Methods of The enviromental design is Randomized Completely Random Design (RAL) single factor (combination of NAA and BAP) consist of 16 treatment with 5 replications and analysed using statistics and DMRT Test at the 5% significance level. The result showed that combination of NAA and BAP had a significant effect on shoot growth 3 days after planting with the best concentration 2 ppm NAA without BAP. Highest number of shoot (47,99 shoot) and highest number of leaves (48,59 leaves) with give of concentration combinations of 1 ppm NAA + 1 ppm BAP. Highest number of root (4,06 root) and highest the length of root (2,46 cm) with concentration of 3 ppm NAA without BAP. Highest of shoot height (1,25 cm) with combination concentration of 2 ppm NAA + 3 ppm BAP